Developing supervision capacity for training rural generalist doctors in small towns in Victoria - Belinda O'Sullivan; Priya Martin; Carla Taylor; Merryn Lodding; Gemma Bilardi; Leanne Dix; Jacque Phillips; Mandy Hutchinson; Rebecca Van Wollingen; Glen Wallace (James Cook University, 2022)
Introduction: Rural generalist (RG) doctors are broadly skilled to provide comprehensive primary care, emergency and other specialist services in small, distributed communities where access is otherwise limited because of distance, transport and cost limitations. In Victoria, Australia, the Victorian Rural Generalist Pathway (VRGP) represents a significant state-wide investment in training and growing the next generation of RGs. The first step of the VRGP is well established through the Rural Community Internship Training program, which commenced in Victoria in 2012-2015; however, the second step (RG2) requires expansion by growing supervised learning in small rural communities where RGs will eventually work. This project aimed to explore enablers and barriers to the supervision of RG2 learners across a core generalist curriculum in distributed towns in three rural Victorian regions. Methods: Data were collected between June and August 2021 through semistructured, in-depth interviews conducted via Zoom or telephone with general practitioners (GPs) and health service executives from small and big health services in the Hume, Loddon Mallee and Barwon South West regions. Interview questions were shared prior to the interview to support reflective responses. Interviews were an hour in length and data were transcribed verbatim and analysed using an inductive thematic analysis process. The research team met regularly throughout the analysis process to refine theme development, test assumptions, and reduce any subjective biases. This study had ethical approval from Monash University. Results: Thirty-one participants, including 13 GPs working at RG scope in MMM 4-7 and 18 health service executives, engaged with RGs consented and participated. The supervision of RG2s was affected by multilayer enablers and barriers. Enablers that emerged were having a critical mass of fellowed doctors using viable models to supervise RG2s, funding for the supervision of RG2s, generalist learning opportunities, and coordination and case management. Barriers included insufficient doctors to supervise, the cost and risk of supervising RG2s, developing rural training but finding it was unattractive to trainees, and a reliance on rotational staff, which limited supervision on the ground. Different regions experienced enablers and barriers to different degrees. Conclusion: Building supervised training for RG2 learners across a generalist scope in distributed rural communities is a complex undertaking, with multilayered enablers and barriers at play. A range of issues are beyond the control of the VRGP and rely on advocacy and collaboration with stakeholders. The major themes suggest that supervised learning should be addressed at multiple levels of the system, the community, clinical settings, and clinicians. Expanding supervision of RG2s across core generalist curriculum in small rural communities will also require a regionally guided long-term vision and stepwise planning. With ongoing commitment to RG-led care, it is possible to achieve high-quality supervision at the RG2 stage, retain RGs on the pathway, and produce skilled RG trainees to serve Victoria into the future.